THE IMPORTANCE OF HALAL CERTIFIED PRODUCTS IN SAMARINDA CITY: IN THE LIGHT OF MAQASID AL-SYARI'AH - Hasan, Maisyarah Rahmi (IAIN Samarinda, 2019)
Halal certification is a guarantee of safety for Muslims to be able to consume a product as evidenced by the inclusion of the halal logo on the product packaging. To realize the